Spectroscopy and modelling of catalyst nanoparticles using STEM-EELS - Sode, J (2020)
This thesis concerns the oxygen reduction reaction (ORR) in the proton exchange membrane fuel cell (PEMFC) and aims to understand the interaction of oxygen with platinum-cobalt (PtCo) catalyst nanoparticles. The techniques employed are aberrated scanning transmission electron microscopy (STEM), electron energy loss spectroscopy (EELS) and modelling through density functional theory (DFT). The comparison of certain features in the experimental and simulated EEL spectra allows for selective optimisation in catalyst design. It is imperative to optimise the design of Pt-based alloys because Pt catalysts are costly. There is also an added advantage of manifold increase in catalytic activity with PtCo alloys in particular.